Intellectual Capital and Agency Conflict - Wijaya, Hendra; Tandelilin, Eduardus; Rahayu, Mudjilah; Hermeindito (Indian Journal of Finance, 2016)
The present research discussed the effect of intellectual capital on agency conflict through investment decision, financing decision, and dividend policy. The research used panel data with a sample of 90 manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2004-2013. The research used three stages least squares estimation technique to test simultaneous model and z-clogg to compare coefficient between the two models. Simultaneous model showed that the negative effect of investment decision, financing decision, and dividend policy on value of a firm reduced with the existence of higher intellectual capital. Based on the analysis, it can be concluded that investment decision, financing decision, and dividend policy showed agency conflict. Higher intellectual capital in a firm helps in reducing the agency conflict in a firm ; so, it can be concludedÂ that intellectual capital can direct management behavior leading to decisions that increase the value of the firm.